2020
DOI: 10.37939/jrmc.v24isupp-1.1453
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Pregnancy Outcome: An Experience in ‘COVID-19 Management Designated’ Tertiary Care Hospital, Rawalpindi, Pakistan

Abstract: Background: The current COVID-19 pandemic has affected almost 17.3 million victims worldwide with mortality of almost 674K. Pregnancy is one of the most susceptible conditions for COVID-19 infection, but limited data is currently available about the clinical characteristics of pregnant women with the disease. Objective; to describe the clinical characteristics, co-morbidities, management, feto-maternal, and neonatal outcome in COVID-19 positive pregnant women. Methodology: A descriptive case series study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…2 patients had PROM butno evidence of perinatal transmission noted. In another local study conducted at Rawalpindi by Syed S. et al, 11 showed good maternal and fetal outcomes in pregnant patients with COVID disease in third trimester. PCR COVID-19 testing was done in 10 neonates and was negative that was similar to the results of our study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…2 patients had PROM butno evidence of perinatal transmission noted. In another local study conducted at Rawalpindi by Syed S. et al, 11 showed good maternal and fetal outcomes in pregnant patients with COVID disease in third trimester. PCR COVID-19 testing was done in 10 neonates and was negative that was similar to the results of our study.…”
Section: Discussionmentioning
confidence: 92%
“…3 Its association with altered immune status like lymphopenia and increase in certain inflammatory markers is similar to that of COVID-19 infection. 11 This, alongside the physiological cardiopulmonary adaptations in pregnancy that is reduced functional residual capacity in lungs and increased oxygen consumption renders pregnant women more susceptible to severe COVID disease.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the pandemic has continued to wreak havoc on the country's already overburdened healthcare system [ 25 ]. Many studies suggest that clinical manifestation of COVID-19 in pregnancy is not different from non-pregnant adults, yet, according to a few studies pregnancy can complicate the clinical course of COVID-19 [ 26 ]. Since our study does not report any COVID-19 case, therefore, no such complication was observed in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[3] The ongoing COVID-19 outbreak has afflicted nearly 17.3 million individuals globally, with about 674000 deaths. [4] Although pregnancy is among the most vulnerable times for individuals suspected/detected with COVID-19 infection, there is currently little information regarding the clinical features of expectant mothers who suffer from COVID-19. [4] Although higher maternal age, presence of comorbidities, and high body mass index have been considered to be the risk factors of severe COVID-19 development among expectant mothers.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Although pregnancy is among the most vulnerable times for individuals suspected/detected with COVID-19 infection, there is currently little information regarding the clinical features of expectant mothers who suffer from COVID-19. [4] Although higher maternal age, presence of comorbidities, and high body mass index have been considered to be the risk factors of severe COVID-19 development among expectant mothers. [5] Because of the physiological modifications in the cardiopulmonary and immunological systems that occur during pregnancy, women are predisposed to respiratory viral infection.…”
Section: Introductionmentioning
confidence: 99%